Evaluation of cardiac troponin I in serum and myocardium of rabbits with experimentally induced polymicrobial sepsis - Tümer, Kenan Çağrı; Özdemir, Haydar; Eröksüz, Hatice (My University, 2020)
Sepsis is a potentially life-threatening condition, and it is frequently complicated by myocardial damage. Data on myocardial damage in rabbit caecal ligation and puncture (CLP) models are limited, although numerous animal models have been used to study sepsis-associated myocardial damage. This study aimed to investigate the effect of CLP on cardiac muscle by measuring serum cardiac troponin I (cTnI) concentrations and by detecting both histopathological changes and cTnI immunoreactivity in cardiomyocytes in rabbits. After CLP was performed in rabbits, blood samples were taken from the jugular vein at 0, 4, 8, and 12 h for haematological and biochemical analyses. At the end of the experiment, all of the rabbits were euthanised to examine the histopathological changes and the cTnI immunoreactivity in cardiac muscle tissue. No changes in serum cTnI concentration were observed in the experimental group (EG) or control group (CG) at 0 and 4 h. In EG, the mean serum cTnI concentrations were 0.230 ± 0.209 and 1.177 ± 0.971 ng/ml at 8 and 12 h, respectively. In CG, the mean serum cTnI concentrations were 0.032 ± 0.014 and 0.031 ± 0.021 ng/ml at 8 and 12 h, respectively. Moreover, cytoplasmic cTnI immunoreactivity decreased in EG compared with that in CG (P<0.01). The results demonstrated that CLP induced a systemic inflammatory response and caused myocardial damage in rabbits.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: caecal ligation and puncture; cardiac troponin I; immunohistochemistry; rabbit; sepsis